Macromol. Rapid Commun. 4/2014. Issue 4 (February 2014) - Ko, Yee Song; Yamamoto, Takuya; Tezuka, Yasuyuki; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> Front Cover: Unprecedented tetracyclic polymer topologies having a spiro‐ and a bridged‐type, quatrefoil form are effectively constructed through an alkyne‐azide, click linking reaction by employing a kyklo‐telechelic poly(tetrahydrofuran), poly(THF), precursor with an azide group, obtained through an electrostatic self‐assembly and covalent fixation (ESA‐CF) process, and complementary tetrafunctional alkyne reagents of either a pentaerythritol derivative or a four‐armed star telechelic polymer precursor. Further details can be found in the article by Y. S. Ko, T. Yamamoto, and Y. Tezuka* on page 412. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>